What determines the composition of international bank flows? - Cornelia Kerl; Friederike Niepmann (Federal Reserve Bank of New York, 2014)
Several recent studies document that the extent to which banks transmit shocks across borders depends on the type of foreign activities these banks engage in. This paper proposes a model to explain the composition of banks' foreign activities, distinguishing between international interbank lending, intrabank lending, and cross-border lending to foreign firms. The model shows that the different activities are jointly determined and depend on the efficiencies of countries' banking sectors, differences in the return on loans across countries, and impediments to foreign bank operations. Specifically, the model predicts that international interbank lending increases and lending to foreign non banking firms declines when banks' barriers to entry rise, a hypothesis supported by German bank-level data. This result suggests that policies that restrict the operations of foreign banks in a country may move activity onto international interbank markets, with the potential to make domestic credit overall less resilient to financial distress.
Keywords: F21; F23; F30; G21; 330; global banks; interbank market; international bank flows; transmission of shocks